Association between serum albumin and glycated hemoglobin in Asian Indian subjects - Tiwari, Shalbha; Botahle, Manish; Hasan, Imtiaz; Kulkarni, Mahesh J.; Sayyad, Mehmood G.; Basu, Rita; Basu, Ananda; Unnikrishnan A. G. (Indian Journal of Endocrinology and Metabolism, 2015)
Protein glycation plays a significant role in diabetic complications. Glycated hemoglobin (HbA1c) is a known predictor of diabetes and its complications. Albumin, found to be profoundly glycated in diabetes, and its level could regulate plasma protein as well as hemoglobin glycation. We aimed to evaluate the association between variations in albumin level with HbA1c in the Asian Indian population. We screened data of 929 subjects who have had a simultaneous measurement of fasting plasma glucose (FPG), HbA1c and albumin levels via the same blood collection. Data were analyzed by SPSS for 610 subjects who met the study criteria. There was a significant negative correlation between HbA1c and albumin concentration (r = -0.284; P < 0.001). Univariate analysis showed the statistically significant decrease of average HbA1c but not for fasting plasma glucose (FPG) across increasing tertiles of albumin. Stepwise multiple regression model showed a significant correlation between HbA1c and serum albumin (P < 0.05), FPG (P < 0.001), hemoglobin (Hb) (P < 0.001) and serum globulin (P < 0.05). FPG was the strongest predictor (63.4%) of variation of HbA1c. The albumin concentration (r = -0.114) accounted for 0.3% (P < 0.05) of the total variance in HbA1c independent of age, body mass index, FPG, Hb, creatinine, total protein and globulin. It was also observed that HbA1c decreases with increasing albumin concentration in those having FPG between 100 to <126 mg/dl. Serum albumin negatively correlates with HbA1c in Asian Indians independent of other variables. This study suggests that predicting diabetes and its complication based on the HbA1c needs to be further investigated in Indian subjects.

Targeted quantification of N-1-(carboxymethyl) valine and N-1-(carboxyethyl) valine peptides of beta-hemoglobin for better diagnostics in diabetes - Jagadeeshaprasad, Mashanipalya G.; Batkulwar, Kedar B.; Meshram, Nishita N.; Tiwari, Shalbha; Korwar, Arvind M.; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (Clinical Proteomics, 2016)
Background: N-1-(Deoxyfructosyl) valine (DFV) beta-hemoglobin (beta-Hb), commonly referred as HbA1c, is widely used diagnostic marker in diabetes, believed to provide glycemic status of preceding 90-120 days. However, the turnover of hemoglobin is about 120 days, the DFV-beta-Hb, an early and reversible glycation product eventually may undergo irreversible advanced glycation modifications such as carboxymethylation or carboxyethylation. Hence quantification of N-1-(carboxymethyl) valine (CMV) and N-1-(carboxyethyl) valine (CEV) peptides of beta-Hb would be useful in assessing actual glycemic status. Results: Fragment ion library for synthetically glycated peptides of hemoglobin was generated by using high resolution-accurate mass spectrometry (HR/AM). Using parallel reaction monitoring, deoxyfructosylated, carboxymethylated and carboxyethylated peptides of hemoglobin were quantified in clinical samples from healthy control, pre-diabetes, diabetes and poorly controlled diabetes. For the first time, we report N-1-beta-valine undergoes carboxyethylation and mass spectrometric quantification of CMV and CEV peptides of beta-hemoglobin. Carboxymethylation was found to be the most abundant modification of N-1-beta-valine. Both CMV-beta-Hb and CEV-beta-Hb peptides showed better correlation with severity of diabetes in terms of fasting glucose, postprandial glucose and microalbuminuria. Conclusions: This study reports carboxymethylation as a predominant modification of N-1-beta-valine of Hb, and quantification of CMV-beta-Hb and CEV-beta-Hb could be useful parameter for assessing the severity of diabetes.
Keywords: Diabetes; Diagnosis; Glycation; Glycemic control; HbA1c; Mass spectrometry

Elevated level of glycated KQTALVELVK peptide of albumin is associated with the risk of diabetic nephropathy - Chaurasiya, Arvindkumar H.; Jaiswal, Meera R.; Bayatigeri, Santhakumari; Kahar, Shweta; Tiwari, Shalbha; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2023)
Diabetic nephropathyis a leading cause of end-stagerenal disease.Hence, early detection of diabetic nephropathy is essential to mitigatethe disease burden. Microalbuminuria, the currently used diagnosticmarker of diabetic nephropathy, is not efficient in detecting it atan early stage. Therefore, we explored the utility of glycated humanserum albumin (HSA) peptides for risk prediction of diabetic nephropathy.Three glycation-sensitive HSA peptides, namely, FKDLG-EENFK,KQTAL-VELVK, and KVPQVST-PTLVEVSR, with deoxyfructosyllysine(DFL) modification were quantified by targeted mass spectrometry (MS)in a study population comprising healthy and type II diabetes subjectswith and without nephropathy. Mass spectrometry, receiver operatingcharacteristic (ROC) curve, and correlation analysis revealed thatthe DFL-modified KQTALVELVK peptide was better than other glycatedHSA peptides and HbA(1c) for identifying diabetic nephropathy.DFL-modified KQTALVELVK could be a potential marker for risk predictionof diabetic nephropathy.

Discovery of free glycated amines and glycated urea in diabetic plasma: potential implications in diabetes - Shaikh, Rashdajabeen Q.; Das, Sancharini; Chaurasiya, Arvindkumar; Ashtamy, Murali G.; Sheikh, Amreen B.; Fernandes, Moneesha; Tiwari, Shalbha; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2024)
The role of protein glycation in the pathogenesis of diabetes has been well established. Akin to proteins, free amino acids and other small-molecule amines are also susceptible to glycation in hyperglycemic conditions and may have a role in the pathogenesis of the disease. However, information about glycation of free amino acids and other small-molecule amines is relatively obscure. In the quest to discover small-molecule glycated amines in the plasma, we have synthesized glycated amino acids, glycated creatine, and glycated urea, and by using a high-resolution accurate mass spectrometer, a mass spectral library was developed comprising the precursor and predominant fragment masses of glycated amines. Using this information, we report the discovery of the glycation of free lysine, arginine, and leucine/isoleucine from the plasma of diabetic patients. This has great physiological significance as glycation of these amino acids may create their deficiency and affect vital physiological processes such as protein synthesis, cell signaling, and insulin secretion. Also, these glycated amino acids could serve as potential markers of diabetes and its complications. While other amines, such as creatinine and urea, accumulate in the plasma and act as biomarkers of diabetic nephropathy. For the first time, we report the detection of glycated urea in diabetic plasma, which is confirmed by matching the precursor and fragment masses with the in vitro synthesized glycated urea by using C-12(6) and C-13(6)-glucose. Further, we quantified glycated urea detected in two forms, monoglycated urea (MGU) and diglycated urea (DGU), by a targeted mass spectrometric approach in the plasma of healthy, diabetic, and diabetic nephropathy subjects. Both MGU and DGU showed a positive correlation with clinical parameters, such as blood glucose and HbA1c. Given that urea gets converted to glycated urea in hyperglycemic conditions, it is crucial to quantify MGU and DGU along with the urea for the diagnosis of diabetic nephropathy and study their physiological role in diabetes.

Autoantibodies against Nε-carboxymethyl lysine and methylglyoxal modified albumin are associated with cardiovascular risk in type 2 diabetes - Patil, Yugendra R.; Tiwari, Shalbha; Momin, Abdulrahaman A.; Unnikrishnan, A. G.; Kulkarni, Mahesh J. (International Journal of Diabetes in Developing Countries, 2025)
{Background Albumin is an abundant plasma protein which gets modified with advanced glycation end products (AGEs) predominantly in diabetic condition. AGE modification induces immune response and autoantibodies are generated which play an important role in disease pathology. Objective This study aimed to illustrate the role of autoantibodies against N epsilon-carboxymethyl lysine (CML) and methylglyoxal (MG) modified albumin in diabetic cardiovascular complications. MethodsType-2 diabetes subjects were enrolled and further grouped into stress test positive or stress test negative based on treadmill stress test (TMT). Autoantibody titer was quantified by ELISA assay for CML-modified albumin (stress test positive
Keywords: AGE; Atherosclerosis; Diabetes; Glycation; Immune response; ROC

Proteome profile of stress test assessed cardiovascular disease risk-prone diabetic subjects - Patil, Yugendra R.; Tiwari, Shalbha; Unnikrishnan, A. G.; Kulkarni, Mahesh J. (Journal of Cardiovascular Translational Research, 2025)
Cardiovascular disease (CVD) is the leading cause of death in the diabetic population. There is a need for specific predictive markers to assess CVD risk. The present study explored the plasma proteome profile of treadmill test (TMT) assessed diabetic stress test positive (DSTP) and diabetic stress test negative (DSTN) subjects by performing a SWATH-MS-based label-free quantitative mass spectrometry approach to identify differentially expressed proteins (DEPs). CVD-relevant DEPs were further validated using a targeted mass spectrometry approach (MRM-HR). It was observed that CO4B, PON1 and LUM exhibited considerable differential expression in both the MS approaches, and ROC analysis showed significant AUC (0.97, 0.79 and 0.77, respectively). Overall, the present study reports these proteins as potential alternative markers for TMT in assessing CVD risk. These markers can possibly overcome the limitations of TMT with further validation in the large cohort.Graphical AbstractAn overview of experimental approaches used in the current study. The study design depicts diabetic subjects assessed for cardiovascular risk by TMT or stress test. The experimental design shows the use of the SWATH-MS approach to identify differentially expressed proteins and validate CVD-related proteins with targeted MS approaches such as MRM-HR. Finally, CO4B, PON1 and LUM exhibited significant AUC in ROC analysis, indicating their potential marker capabilities to predict CVD in diabetic subjects.
Keywords: cardiovascular disease; Diabetes; Multiple reaction monitoring; Plasma markers; Proteome profile; Quantitative mass spectrometry